Kidney adverse events from tyrosine kinase inhibitors - Narongkiatikhun, Phoom; Noppakun, Kajohnsak (Journal of the Nephrology Society of Thailand, 2022)
Tyrosine kinase inhibitors (TKIs) are one of the oncologic molecular targeted therapies interfering with cellular signal transduction by inhibiting the phosphorylation of tyrosine residue within substrate protein, resulting in down regulating cell proliferation and cell differentiation processes. Currently, TKIs are widely used to treat various types of malignancy due to their benefit of delaying tumor progression and increasing patient’s survival compared with conventional chemotherapies. Nonetheless, a large number of publications have reported kidney complications associated with these drugs including but not limited to acute kidney injury, acute glomerulonephritis, nephrotic syndrome, and electrolyte imbalances. Hence, awareness of these complications and regular laboratory monitoring is crucial for early detection in these groups of vulnerable patients. This article aimed to review the current data of TKIs on kidney complications regarding pathophysiology, management, and monitoring strategies. Also, a case is presented of one patient with gastrointestinal stromal tumor (GIST) at the stomach received sunitinib and developed acute kidney injury and nephritonephrotic syndrome suspected from TKIs.